2006
DOI: 10.1002/mrd.20499
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of female primordial germ cells in the male testes of chicken (Gallus gallus domesticus)

Abstract: In our previous studies, we demonstrated that female primordial germ cells (PGCs) have the ability to differentiate into W chromosome-bearing (W-bearing) spermatozoa in male gonads of germline chimeric chickens. In this study, to investigate the differentiation pattern of female PGCs in male gonads in chickens, three germline chimeric chickens were generated by injecting female PGCs into the male recipient embryos. After these male chimeras reached sexual maturity, the semen samples were analyzed for detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
(36 reference statements)
0
32
0
Order By: Relevance
“…Tagami et al [24] reported that female PGCs (ZW germ cells) could differentiate into both Z-bearing and W-bearing spermatozoa in the male testis. Concomitantly, however, they assumed that ZW germ cells were restricted at some point during spermatogenesis.…”
mentioning
confidence: 99%
“…Tagami et al [24] reported that female PGCs (ZW germ cells) could differentiate into both Z-bearing and W-bearing spermatozoa in the male testis. Concomitantly, however, they assumed that ZW germ cells were restricted at some point during spermatogenesis.…”
mentioning
confidence: 99%
“…The frequency of donor-derived offspring from germline chimeras is significantly higher for donor PGCs and recipient embryos of the same-sex compared with different-sex combinations (Naito et al, 1999). Tagami et al (2007) reported that female PGCs in male gonads passed through the first and second meiotic divisions by adapting themselves to the male environment; however, their ability to complete spermatogenesis was limited. Therefore, it is thought that there is some possibility of mixture sex.…”
Section: Discussionmentioning
confidence: 99%
“…When female PGCs (ZW) were transferred to male recipient embryos, Z-bearing spermatozoa derived from female PGCs could be produced to give rise to functional offspring. W-bearing spermatozoa were also produced, but no functional offspring have been generated so far from the mixed-sex germline chimeric chickens (Kagami et al, 1995(Kagami et al, , 1997Tagami et al, 1997Tagami et al, , 2007Naito et al, 1999). Recently, gonadal germ cells isolated from the gonads of 7-day incubated embryos were transferred to the recipient embryos and succeeded to produce same-sex and mixed-sex germline chimeric chickens (Nakajima et al, 2014).…”
Section: Germline Chimeric Chickensmentioning
confidence: 99%